Preparing Student Mobility Through a VR Application for Cultural Education - Pappa, Giouli; Ioannou, Nikoletta; Christofi, Maria; Lanitis, Andreas (My University, 2018)
The potential of VR as a basis for developing dedicated applications for Cultural Education is explored through the design and development of a VR application called Celestial Breeze. Celestial Breeze is a dedicated application that aims to provide knowledge about the culture of different European countries. The design of the application is based on multimedia learning theories in an attempt to maximize the learning outcomes of the users. Emphasis is given in examining the effectiveness of Celestial Breeze as a tool of information dissemination in relation to the age and gender of the audience. We evaluated the application through a user study with 20 participants - half of whom were under aged- but all belong to Generation Y. The comparison of pre- and post- test results pinpoints the positive learning outcomes of Celestial Breeze on participants indicating in that way the potential of using immersive applications for cultural education.
Keywords: Cultural heritage; Culture; Generation Y; Intangible heritage; Learning principles; Multimedia design; Social etiquette; Tangible heritage; Virtual reality; Virtual worlds